Efficacy and safety of glecaprevir and pibrentasvir in Japanese patients with hepatitis C virus infection aged 75 years or older - Yuri Komaki (BMC Gastroenterology, 2022)
Abstract Background It is estimated that approximately 50% of patients with hepatitis C virus (HCV) infection in Japan are currently over 75 years old. However, patients aged ≥ 75 years are typically underrepresented in clinical trials of direct-acting antivirals. This study aimed to evaluate the efficacy and safety of glecaprevir and pibrentasvir (G/P) treatment in Japanese patients with HCV infection aged ≥ 75 years. Methods This multicenter, retrospective study included 271 Japanese patients with HCV infection from 12 centers in Miyazaki Prefecture, Japan. Demographic, clinical, virological, and adverse events (AEs) data obtained during and after G/P treatment were collected from medical records. The patients were divided into two groups: younger (n = 199, aged < 75 years) and older (n = 72, aged ≥ 75 years). Virological data and AEs were analyzed according to the age group. Results In intention-to-treat (ITT) and per-protocol analyses, the overall sustained virological response 12 (SVR12) rates were 93% and 98.8%, respectively. Two patients in the older group and 14 patients in the younger group dropped out before SVR12 assessment. Although patients in the older group tended to have liver cirrhosis, 95.8% in the older group and 92% in the younger group achieved SVR12 in the ITT analysis (P = 0.404). In total, 48 (17.7%) patients experienced treatment-related AEs. Common AEs during treatment included pruritus, headache, and fatigue. The AEs were not significantly different between the two groups. Conclusions Compared with younger patients, older patients showed similar virological response and tolerance to G/P treatment.